Persepsi Pengunjung terhadap Objek Wisata di Pulau Pasumpahan Kota Padang Sumatera Barat - Musena, Ariska; Mariya, Sri (Lembaga Yasin AlSys, 2025)
This study aims to determine the perception of visitors to tourist attractions on Pasumpahan Island, Bungus Teluk Kabung District, Padang City, West Sumatra. The method used in this study uses a quantitative method carried out with 100 respondents. Data collection techniques in this study used observation, questionnaires, and documentation. Data analysis used Descriptive Analysis Test with calculations using the Exxel formula and spss 23.0. The results of this study indicate that visitor perceptions of tourist attractions on Pasumpahan Island are seen from 4 aspects, namely, 1) Attractions, are in the strongly agree category with an average of 4.50 2) Accessibility, are in the strongly agree category with an average of 4.46 3) Amenities, are in the good category with an average of 3.99 4) Ansileri are in the good category with an average of 4.14 with a percentage of 70% very good, and 30% good. So the final result shows that overall the Pasumpahan Island tourist attraction has met the four aspects of tourist attractions. This is shown in the very good category with a percentage of 70%.